Topography-driven movement of biomolecular condensates - Matthias Pöllmann; Katja Zieske (PLoS ONE, 2026)
Biomolecular condensates are assemblies of proteins or nucleic acids that exhibit liquid-like properties and organize intracellular biochemical reactions within many cells. Some condensates require membrane association, and we previously developed an assay to reconstitute biomolecular condensates in the presence of various membrane topographies. However, the effect of membrane topography on the displacement of biomolecular condensates remains incompletely understood. Here, we studied the movement of biomolecular condensates on lipid membrane-clad microstructures in a cell-free assay. We observed movements perpendicular to microstructured surfaces opposing gravitational force for untethered condensates. Increased membrane attachment reduced the number of such movements. These movements were observed for liquid-like condensates as well as for more viscous condensates, on surfaces with grooves and in cylindrical microstructures with varying diameter. A passivating PEG-coating of the microstructures also enabled movements of the condensates perpendicular to microstructured surfaces, further confirming the role topography of modulating passive condensate movement. An increased wetting of condensates on microgrooves led to the formation of elongated condensates which exhibit a coordinated sideward movement upon fusion. Our results indicate that membrane topographies, in combination with membrane attachment patterns, regulate passive biomolecular condensate movement.